The effects of gamification on antimicrobial resistance knowledge and its relationship to dentistry in Saudi Arabia: a randomized controlled trial - Khalid Aboalshamat; Amjad Khayat; Ragheb Halwani; Ammar Bitan; Ryyan Alansari (BMC, 2020)
Abstract Background Antimicrobial resistance (AMR) has reached alarming levels and is considered to be a worldwide public health problem. One of the most significant factors contributing to the spread of AMR is the lack of proper knowledge about the use of antibiotics, which are being used more frequently in dentistry. Recent studies have found that gamification shows promising results for helping the average person improve their knowledge about health and may also be used to boost knowledge about AMR among the public. This study aimed to assess the effects of gamification on AMR awareness, using a board game to promote knowledge about AMR among the public in Saudi Arabia. Methods Using a single-blinded parallel group randomized controlled trial design, 94 volunteers were recruited and randomized into two groups. The study group received information about AMR by playing a board game, while the control group received the same information given in a conventional lecture. The participants were evaluated three times: (T1) before the intervention, (T2) immediately after the intervention, and (T3) one month after the intervention for follow-up to evaluate their retention of the information. Results Results showed that there were significant improvements (p <  0.05) in knowledge scores for T2 and T3 in comparison to the T1 baseline scores in both groups. However, the knowledge scores also relapsed significantly from T2 to T3 in both groups. Nevertheless, the difference in knowledge score T1 to T3 was significantly higher in the study group in comparison to the control group, and the participants had higher mean scores to use the game as health promotion method. Conclusions Gamification using a board game can significantly improve AMR knowledge, with better retention than conventional lecture. It is a promising method for boosting public knowledge about AMR and its relationship to dentistry. Trial registration ISRCTN registry: ISRCTN15884410 (retrospectively registered 26-October-2019).